Multiproxy approach for Holocene paleoenvironmental reconstructions from microorganisms (testate amoebae and foraminifera) and sediment analyses: The infilling of the Loire Valley in Nantes (France). (March 2015) - Delaine, Maxence; Armynot du Châtelet, Eric; Bout-Roumazeilles, Viviane; Goubert, Evelyne; Le Cadre, Valérie; Recourt, Philippe; Trentesaux, Alain; Arthuis, Rémy
Foraminifera and testate amoebae are jointly used with sediment characteristics (sediment size, calcium carbonate, C, H, N and S proportions, and clay mineralogy) to reconstruct the Holocene sediment infilling of the Loire estuary (Nantes, France). The results reveal the infilling of the Loire Valley during the Holocene. Deposited on the Hercynian substratum, the first deposits are made of gravels with rare associated fauna. This corresponds to the gravel lag usually present as basal deposits in the river course. The clay mineralogy indicates an erosion of the substratum. Then, from 8850 to 5850 cal. yr BP, estuarine fauna settled in a laminated sediment that alternates between clay and sand. The smectite associated with kaolinite and illite suggests increased input from the Sèvre Nantaise River. The fauna progressively shifts from estuarine to marine, indicating a rise in the sea level. From 5850 cal. yr BP, the pace of the sea level rise slowed and channels migrated, implying intense erosion. After 2100 cal. yr BP, the fauna was dominated by testate amoebae, indicating a continentalization of the environment. The top samples reflect recent human activity and urbanization.